Skills and Literacy Training for Better Livelihoods : A Review of Approaches and Experiences - Oxenham, John (World Bank, Washington, DC, 2012)
Too often, policy for vocational education in developing countries has only concerned itself with a literate minority within the labor force. This study helps to widen that view. From the perspective of " Education for All " and " Lifelong Education, " the report examines efforts to combine vocational training with literacy education, to enable a very poor, illiterate labor force, especially rural women, to develop more productive livelihoods and take on increasingly active roles in transforming their families and communities. The aim is to assess whether and how official policy should support such efforts. Based on documentary evidence from several countries, particularly Guinea, Kenya, Senegal, and Uganda, the report suggests that vocational education policy should encompass out-of-school, and illiterate youth and adults, but to be effective would require gradualism, decentralization, capacity building, flexibility, and components of savings, credit, and enterprise development.